Job satisfaction among selected academic librarians in Metro Manila - Macapagal, Karen I.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study is about the job satisfaction levels among academic librarians in Metro Manila. Job satisfaction was grouped in two categories, job content which are aspects involved directly with work and job context which involves aspects outside of the actual work, extrinsic qualities. The author wanted to find out which aspects academic librarians feel more satisfied. Also, the preference among the nineteen dimensions included in both content and context aspects were ranked. There were five main hypotheses tested.
The two-tailed two sample t test for determining difference between means was used for independent variables age, gender and civil status. While, a one-tailed two sample t test was used for testing educational attainment and job title variation.
The t test results show that there is no significant difference between the context/content satisfaction ratios between older and younger academic librarians. Also, there is no significant difference in the job context satisfaction average to job context satisfaction average ratio among male and female academic librarians. The third null hypothesis was also retained. There is no significant difference in the context/content ratio between married/widowed and single academic librarians. Fourth, there is no significant difference in the context/content ratios between higher-educated and lower-educated academic librarians. Lastly, that there is no significant difference between the context/content ratios of higher-positioned and lower positioned academic librarians.
Among the preferences, sense of achievement ranked highest in the list followed by job security, sense of recognition, salary and opportunity for advancement. Although it was never established that academic librarians of varying background profiles have different context/content satisfaction levels, it is true that their needs still differ. Their needs do not end in the dimensions mentioned by Herzberg. They must be satisfied on all aspects of their life.
The recommendation is that for supervisors to always motivate their employees into bringing out their fullest potentials possible especially since the field of librarianship is a form of public service.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Job satisfaction -- Philippines -- Manila Metropolitan Area; Libraries -- Philippines -- Manila Metroplitan Area